Женская месть - Робертс Нора (Романтическое настроение, 2014)
Экземпляры: Ф. 4 (20191030) / Инвентарный номер: 47293 / Цена: 30.00 / Сис.шифр: И(Амер.) / Авт.знак: Р 58 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)